Rural Consumers’ Behaviour Regarding Non Durable Goods: A Study in Erode District of Tamil Nadu - Selvaraj, A. (Indian Journal of Marketing, 2007)
Marketing plays a pivotal role in the growth and development of a country irrespective of size, population and the concepts are so interlinked that, in the absence of one, another virtually cannot survive. It is a historical fact that the development of marketing has always kept pace with the Economic growth of the country. Both have experienced evolutionary rather than revolutionary change. The objective of modern marketing is to make profits through satisfying consumer’s needs and wants. Hence, the marketers have to understand the real needs, wants, beliefs and attitudes of the consumers towards their products and services. Today, network marketing is a multi-billion dollar business. A number of companies have adopted this business model. It has grown into one of the driving forces of the 21st century economy. Network marketing is now regarded by many business leaders as the business for future. But this marketing method was misunderstood as a get rich-quick scheme. It is also too common for network marketer’s world wide to answer the legality and soundness of their business.